Recensioni - Micheletta, Luca; Girardi, Edoardo; Moretti, Jacopo; Bianchi, Giulia; Natale, Deborah; Fraioli, Francesco Romano; Giachetti, Fulvia; Lucchini, Andrea; Marilungo, Sara; Valente, Michaela (Studi Politici, 2024)